Pengaruh Kedalaman Sudu Mangkok terhadap Unjuk Kerja Turbin Kinetik - Fitriansyah, Erwin; Wahyudi, Slamet; Winarto, Winarto (Jurnal Rekayasa Mesin, 2020)
The purpose of this study was to determine the effect of depth variations of the bowl blade on the performance of kinetic turbines. The test has conducted experimentally on a laboratory scale. In this study three vertical shaft, kinetic turbines were used with blade depth variations of 2 cm, 3 cm, and 4 cm. Each turbine will be tested on different rotation variations and flowrate variations. Parameters such as turbine power and efficiency will be determined based on the results of measurements of water velocity, water level, and braking load. The results showed that the depth of the bowl blade affected the performance of the kinetic turbine. The highest kinetic turbine performance was obtained in the turbine with 4 cm blade depth variation, followed by the turbine with 3 cm blade depth variation and the lowest turbine performance was obtained at 2 cm blade depth variation. The maximum performance of the turbine is obtained at 4 cm blade depth variation at 80 rpm and 65 m3/h water discharge, where the power generated is 13.2 Watts and efficiency is 34.5%.